Fluvial transport of impact evidence from cratonic interior to passive margin: Vredefort-derived shocked zircon on the Atlantic coast of South Africa - Montalvo, S.; Cavosie, Aaron; Erickson, T.; Talavera, C. (Mineralogical Society of America, 2017)
Meteorite impacts produce shocked minerals in target rocks that record diagnostic high-pressure deformation microstructures unique to hypervelocity processes. When impact craters erode, detrital shocked minerals can be transported by fluvial processes, as has been demonstrated through studies of modern alluvium at some of the largest known impact structures. However, the ultimate fate of distally transported detrital shocked minerals in fluvial systems is not well understood and is an important parameter for constraining the location of a source crater. In South Africa, detrital shocked minerals from the 2020 Ma Vredefort impact structure have been documented in the Vaal River basin, downriver from the structure. Here, we report results of an extensive microstructural survey of detrital zircon from the Orange River basin and the Atlantic coast of South Africa to search for the presence of far-traveled Vredefort-derived detrital shocked zircon grains in different modern sedimentary environ - ments. Three shocked grains were found out of 11 168 grains surveyed (0.03%) by scanning electron microscopy, including two in beach sand on the Atlantic coast and one from a sandbar 15 km upstream from the mouth of the Orange River. Shock-produced {112} twins documented by electron backscatter diffraction in each of the three grains confirm their impact provenance, and U-Pb ages from 3130 to 3040 Ma are consistent with derivation from bedrock at the Vredefort impact structure. These results demonstrate the transport of Vredefort-derived shocked zircon to the coast via the Vaal-Orange river system, which requires 1940 km of fluvial transport from their point source on the Kaapvaal craton to the Atlantic coast passive margin. These results further demonstrate that shocked zircon grains can be detected in detrital populations at abundances <1%, and can ultimately be transported outside their basin of origin when they arrive at continental margins. Detrital shocked zircon thus constitutes long-lived evidence of former impacts, as they retain microstructural evidence of shock deformation, as well as geochemical (U-Th-Pb) fingerprints of their source terrain. The study of detrital shocked minerals uniquely merges impact cratering with sedimentology, as identification of detrital grains with diagnostic shock microstructures in siliciclastic sediments can be applied to search the sedimentary record for evidence of eroded impact structures of any age, from the Phanerozoic to the Hadean, which can aid in reconstructing the impact record of Earth.